The MPA's Leadership Style in Community-Based Forest and Land Fire Management - Kushartati Budiningsih; Elvida Yosefi Suryandari; Ane Dwi Septina (Jurnal Penelitian Kehutanan Wallacea, 2020)
Community involvement in forest and land fires management at site level is important due to the community can play a central role in preventing forest and land fires. One of the programs that involves the community in controlling forest and land fires is the Fire Care Community or Masyarakat Peduli Api (MPA). The MPA institution is a group consisting of members who join voluntarily. As a organization, MPA requires leadership that is able to mobilize members to carry out their role. MPA Wonorejo in Musi Banyuasin Regency, South Sumatra Province, is one of the successful MPAs. In this case the leader of MPA Wonorejo received the Wana Lestari award from the Minister of Environment and Forestry in 2018. With the case study method, this research was conducted to explore the leadership style that has been applied to the Wonorejo MPA. The results showed that MPA Wonorejo's leadership style is a transformational style with charismatic characters, inspires members, encourages intellectuality and provides individual attention. The leader of MPA has an important role in mobilizing MPA members to play a role in fire control.